Human immunodeficiency virus in Saudi Arabia: Current and future challenges - Maha Al-Mozaini; Tahani Al-Rahabani; Qais Dirar; Tala Alashgar; Ali A. Rabaan; Waleed Murad; Jawaher Alotaibi; Abdulrahman Alrajhi (Elsevier, 2023)
Introduction: Understanding the pathophysiology of HIV infection has been crucial to the design of effective anti-viral strategies. HIV infection is declining worldwide due to early diagnosis and the effective long-term use of anti-retroviral therapy. New infections decreased from 3.3 million in 2002-2.3 million in 2012. However, in the Middle East and North Africa (MENA), an estimated 83,000 individuals still acquired the virus, with 37,000 morbidities reported. The first incidence of acquired immunodeficiency syndrome (AIDS) from the Kingdom of Saudi Arabia (KSA) was reported in 1984. By the end of 2013, around 1509 patients had been diagnosed with HIV infection. HIV surveillance has improved in KSA with advances in medical care, counseling, family planning, diagnostic evaluation, and anti-retroviral therapy, but challenges remain. Patients receiving anti-retroviral therapy still show significant morbidity and mortality. Further targeted treatment regimens and preventive strategies are required to control HIV infection in KSA. Progress towards meeting the 90-90-90 goals for HIV in the MENA has also not been systematically monitored. Method: In this review, we examine current screening programs, therapeutic modalities, the emergence of drug resistance, and future perspectives for HIV-associated health care in KSA. Conclusion: The aim is to offer insight for healthcare policymakers to comply with the UNAIDS 2020 vision program and help establish the prevailing paradigms in the HIV community for an AIDS-free generation and the 90-90-90 goals for diagnosis.